Efficiency of beef production systems: Description and preliminary evaluation of a model - Naazie, A.; Makarechian, M.; Hudson, R.J. (Elsevier, 1997)
A deterministic beef efficiency model (BEM) was developed for investigating production efficiency. Efficiency was defined, over the lifetime of the herd, as a ratio of total output (lean meat equivalent) from the herd to total input (feed equivalent in Mcal metabolizable energy, ME) to the herd, and has units of g lean meat Mcal -1 ME. The model combines three tandem submodels describing: (1) growth and feed intake, (2) herd structure, and (3) enterprise efficiency. It is capable of investigating efficiency of production in traditional cow-calf systems, dairy-beef systems as well as systems where an offspring's sex-ratio at birth is controlled. It treats the female and her offspring as the basic herd unit and evaluates efficiency in relation to how long the cow stays in the herd (age at culling) and the degree of maturity of her offspring when marketed, Procedures for validating and evaluating behaviour of a beef efficiency model are described. The model was most sensitive to the degree of maturity of the dam. Increasing the dam's maturity by 10% resulted in a large (up to 35%, depending on breed group) decline in efficiency. The model was moderately sensitive to maturing rate and carcass lean content but was not sensitive to mature size or the inflection parameter. Increasing the maturing rate or lean content by 10% results in up to 8.7% increase in efficiency.